Resistance of direct metal laser sintered Ti6Al4V alloy against growth of fatigue cracks. (November 2017) - Konečná, R.; Kunz, L.; Bača, A.; Nicoletto, G.
Highlights: Fatigue crack growth in DMLS produced Ti6Al4V is independent on build direction. Resistance to fatigue crack growth of DMLS and conventionally manufactured Ti6Al4V is similar. The threshold value of the stress intensity range for Ti6Al4V is 3.7 MPa m 1/2 . Abstract: Growth of long fatigue cracks in Ti6Al4V alloy prepared by selective laser melting technology was experimentally investigated. CT specimens were manufactured by direct metal laser sintering (DMLS) on EOSINT M270 system. CT specimens having three different crack orientations with respect to the DMLS build direction were manufactured with the aim to check the influence of directionality of microstructure of the DMLS material on the growth of long fatigue cracks. It was experimentally found that there is no influence of the build orientation and related directionality of the microstructure on tensile properties, growth of long fatigue cracks and crack propagation threshold, when optimal DMLS process parameters setting is used and subsequent stress relieving heat treatment at 380 °C for 8 h is applied on the build material. The experimentally determined fatigue crack growth curve for Ti6Al4V manufactured by DMLS technique was compared with available literature data and with data for conventionally forged material. The fatigue crack propagation path and fracture surfaces were investigated with the aim to analyze the influence of the specific microstructure produced by the DMLS on the mechanism of the propagation of long cracks.